Propensity to environmentally responsible consumption: a study with adolescents (Gestão & Regionalidade, 2016)
Young people born in the late 1990s have received much information about sustainability, which is considered fundamentalin the formulation of a new mentality of consumer education. But how these young people behave in relation to theenvironment? The aim of this study was to examine the propensity of young secondary students towards environmentallyresponsible consumption. For this, a scale tested and considered adequate to measure it was used, in addition to profile variablesidentified as influential in the literature. A survey was carried on with 138 students in a public high school in the cityof Jaguariúna (SP). Results show that the only variable of the profile with discriminatory power to measure the propensity tothe responsible consumption is gender. Furthermore, it was found that of the 40 items used in the scale, four are determinantsto measure the propensity towards environmentally responsible consumption, which two are concerned to personalbehavior and two are regarding to financial efforts. One of the most important contributions of this study is the propositionof a model that can be used in the future to follow the effect of environment education of youth and of the changes onattitudes of these future customers.